Lobe identity in the Mongolian gerbil prostatic complex: A new rodent model for prostate study - Rochel, Sabrina Santos; Bruni-Cardoso, Alexandre; Taboga, Sebastiao Roberto; Leite Vilamaior, Patricia Simone; Goes, Rejane Maira (Wiley-Blackwell, 2007)
Knowledge of structural and physiological differences among the prostatic lobes (PL) is the basis for development of experimental studies in traditional laboratory rodents. Although Mongolian gerbil reproductive organs have been increasingly investigated, its prostate structure is far from being properly known, and investigations of this organ focused on the ventral lobe (VL). Thus, the present study provides a thorough morphological description of prostatic complex in the male adult gerbil on the basis of topographic, histological, and ultrastructural analysis and ductal branching. Like other rodents, four pairs of PL were observed. However, in contrast to the rat and mouse, the VL is the least voluminous component and the dorsolateral lobe (DLL) is the most prominent and spatially isolated from remaining PL. The occurrence of a dorsal lobe (DL), hidden between bladder and insertion of seminal vesicles, has not been mentioned in previous reports with Mongolian gerbil. Collagenase digestion followed by microdissection revealed that, except for DL, which has a tubularacinar organization, all PL exhibit tubular organization and variable ductal branching. Distinct histological and ultrastructural features such as secretory epithelium, aspect of luminal secretion and stromal organization are reported for each PL and are confirmed by morphometric and stereological methods. Histological sections showed at least three intralobar segments in VL and DL. Ultrastructural analysis evidenced that, although luminal epithelial cells of PL share typical features of exocrine secretory cells, there are striking lobe phenotypical variations. Both merocrine and apocrine pathways are observed in variable rates in all PL, with the predominance of the former in the DLL and the latter in the CG. The morphological observations presented herein point to distinct structural identities for each PL, which probably reflects,specific functional compromise of seminal fluid secretion. These data also point to the gerbil as a good model for investigations concerning the regulation of prostate development and homeostasis, mainly with regard to the dorsal and dorsolateral PL.
Keywords: prostate lobes; gerbil; ductal branching; intralobar; variations; ultrastructure